Planning: A Tool for Administration of Teachers’ Competence Development Programmes for Improved Service Delivery in Secondary Schools in Rivers State, Nigeria. - Ukaigwe, P. C.; Igbozuruike, Innocent U. (Advances in Social Sciences Research Journal, 2019)
The study examined the role of planning in the administration of Teachers Competence Development Programmes (TCDPs) for improved service delivery in secondary schools in Rivers State, Nigeria. The descriptive research design was adopted for the study. The population of the study consisted of 274 principals in public secondary schools in Rivers State. A sample size of 130 principals was drawn using proportionate random sampling technique. A validated questionnaire instrument titled “Principals’ Decision-making and Interpersonal Skills for Effective Administration of Public Secondary Schools Questionnaire’ (PDISEAPSSQ)” was used to generate data used in the study. The instrument has reliability index of 0.83, using test retest test method. The research questions were analysed and answered using mean and mean-set, whereas the research hypotheses were tested using z-test statistics at 0.05 alpha level. The findings of the study showed that TCDPs helped to increase the competencies of teachers in the areas of teaching skills, communication skills and classroom management skills, lesson planning skills and enabling attributes. This study revealed that adequate planning of TCDPs ensures that selected programmes are goal directed and ensures that needs of learners are determined from the onset so that the objectives of TCDPs are tailored accordingly. The findings of the study also showed that proper planning of TCDPs ensures that the required resources for successful implementation of TCDPs plans are earmarked and set aside for the designated purposes. Recommendations made among others included that, educational planners and administrators who are responsible for TCDPs in the State Ministry of Education should design and integrate programmes that will address the deficiencies of teachers in subject-specific areas, and also make similar arrangements directed at educating teachers on how to use ICT facilities to research and teach easily.